Answer:9.51
Step-by-step explanation:You add them for the total
Answer: 11
=========================
Explanation:
To find the inverse, or f^-1 of a function, you first replace the y= 6x-4 with x=6y-4
Finding the inverse from here is basically just finding y in terms of x.
1) x=6y-4
2) x+4=6
3) (x+4)/6= y
y= (x+4)/6 is now your f^-1.
Now that you have your inverse, replace 62 with your x in y=(x+4)/6
1) (62+4)/6
2) 66/6
3) 11
Therefore, f^-1(62)= 11
Hope this helps :)
173888888888888888888888888888
The probability would be 1/4 for hearts 1/13 for the number card I think this is right sorry if it’s not
<span>Simplifying
3a2 + -2a + -1 = 0
Reorder the terms:
-1 + -2a + 3a2 = 0
Solving
-1 + -2a + 3a2 = 0
Solving for variable 'a'.
Factor a trinomial.
(-1 + -3a)(1 + -1a) = 0
Subproblem 1Set the factor '(-1 + -3a)' equal to zero and attempt to solve:
Simplifying
-1 + -3a = 0
Solving
-1 + -3a = 0
Move all terms containing a to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 1 + -3a = 0 + 1
Combine like terms: -1 + 1 = 0
0 + -3a = 0 + 1
-3a = 0 + 1
Combine like terms: 0 + 1 = 1
-3a = 1
Divide each side by '-3'.
a = -0.3333333333
Simplifying
a = -0.3333333333
Subproblem 2Set the factor '(1 + -1a)' equal to zero and attempt to solve:
Simplifying
1 + -1a = 0
Solving
1 + -1a = 0
Move all terms containing a to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1 + -1a = 0 + -1
Combine like terms: 1 + -1 = 0
0 + -1a = 0 + -1
-1a = 0 + -1
Combine like terms: 0 + -1 = -1
-1a = -1
Divide each side by '-1'.
a = 1
Simplifying
a = 1Solutiona = {-0.3333333333, 1}</span>